2011
DOI: 10.1016/j.psychres.2011.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Healthy people with delusional ideation change their mind with conviction

Abstract: Emotional distress and reasoning biases are two factors known to contribute to delusions. As a step towards elucidating mechanisms underlying delusions, the main aim of this study was to evaluate a possible "jumping to new conclusions" reasoning bias in healthy people with delusional ideation and its association with emotions. We surveyed 80 healthy participants, measuring levels of depression, anxiety, cognitive error and delusional ideation. Participants completed two versions of the beads task to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
1
12
0
2
Order By: Relevance
“…For example, non-clinical studies that reported more JTC in delusion-prone than non-delusion-prone individuals tended to adopt a percentile split, yielding two non-clinical groups more widely apart on delusion-proneness than studies using a median split [ 19 , 21 ]. However, studies that investigated the link between JTC and delusion-proneness based on median split grouping or correlation approaches did not provide consistent results [ 20 , 22 , 23 , 25 , 28 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, non-clinical studies that reported more JTC in delusion-prone than non-delusion-prone individuals tended to adopt a percentile split, yielding two non-clinical groups more widely apart on delusion-proneness than studies using a median split [ 19 , 21 ]. However, studies that investigated the link between JTC and delusion-proneness based on median split grouping or correlation approaches did not provide consistent results [ 20 , 22 , 23 , 25 , 28 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 48 ]). Similarly, clinical and non-clinical studies using multi-dimensional measures found inconsistent results regarding the association between JTC and dimensions of delusions [ 22 , 23 , 49 ]. We did not find a closer link between JTC and delusional ideation in the clinical group as compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindez speciálisan kifejlesz tett tesztekkel igazolható, ahol bizonyos számú golyó húzás után kell eldönteni, hogy az melyik konténerből származik (beads task) [9]. A közelmúlt metaelemzése (n = 2237) adatokat szolgáltat arra, hogy a fenti tesztben a döntés előtt kért gyöngyök (golyók) száma (adatgyűj tés) és a skálával megítélt téveszmés gondolkodás mérté ke közötti összefüggés negatív korrelációt jelez, azaz a súlyosabb állapot kevesebb adatgyűjtést feltételez a dön téshozatalhoz [10].…”
Section: A Paranoia Kialakulásának Tényezőiunclassified
“…Ez már nyilván extrém pszichotikus mélységű torzulása a gondolkodásnak, ahol az önértéke lészavar bűnösségi téveszméig fokozódott. Tanulmá nyok szerint a depresszió és kognitív torzítás előre jelez ték a paranoid gondolkodást, de nem az okfejtési/ érvelési stílust [9]. Az is megfogalmazható, hogy az 'ál landó aggódás, aggodalmaskodás paranoiához vezethet'.…”
Section: A Paranoia Kialakulásának Tényezőiunclassified